SDRs, Currencies, and Gold : Sixth Survey of New Legal Developments - Gold, Joseph (Pamphlet Series; Pamphlet Series, ;, 1983)
This paper presents the sixth survey of developments in international and national monetary law and practice involving special drawing rights (SDRs), currencies, and gold. The paper highlights that a member's currency held by the IMF in accounts other than the General Resources Account is not subject under the IMF's Articles of Agreement to the principle of maintenance of value in terms of the SDR that applies to currency held in the IMF's General Resources Account. The IMF has express or implied powers to invest holdings in accounts to which no obligation to maintain value is attached.